Bycatch reduction in the deep-water shrimp (Pandalus borealis) trawl fishery with a large mesh top panel - Cerbule, Kristine; Jacques, Nadine; Pettersen, Hermann; Ingólfsson, Ólafur Arnar; Herrmann, Bent; Grimaldo, Eduardo; Larsen, Roger B.; Brinkhof, Jesse; Sistiaga, Manu; Lilleng, Dagfinn; Brčić, Jure (Journal for Nature Conservation, 2021)
In the Northeast Atlantic deep-water shrimp (Pandalus borealis) trawl fishery, the bycatch of juvenile fish and shrimp represents a problem. This study evaluated if inserting a 200 mm mesh size top-panel in the last three sections of the tapered upper belly section of the trawl could reduce bycatch of juveniles while maintaining the catch efficiency for deep-water shrimp. The bycatch species investigated were Greenland halibut (Reinhardtius hippoglossoides), redfish (Sebastes spp.) and polar cod (Boreogadus saida). The bycatch of Greenland halibut and the smallest polar cod was significantly reduced, while no effect was found for redfish. The large mesh panel did not lead to a significant loss of deep-water shrimp. The results of this study illustrate how a simple modification of a fishing gear can mitigate the bycatch problem in a shrimp fishery, without significant losses of the target species.